A year in photography : Magnum archive - Biebuyck, Marie-Christine; Kordick, David (Prestel ; Paris ; Magnum Photos, 2013)
"Presents some of the greatest images from Magnum, the world's most prestigious photo agency. Covering over 60 years and almost the entire globe, these 365 iconic moments are guaranteed to inspire and amaze you." -- Cover, p. [4]